Pengaruh Substitusi Jagung dengan Corn Gluten Feed (CGF) dalam Ransum terhadap Kualitas Karkas Babi dan Analisis Ekonomi - P H Siagian; S Natasasmita; P Silalahi (Media Peternakan, 2005)
This research was conducted to evaluate the effect of corn gluten feed as corn substitution in the rations on swine carcass quality and economic analysis. The rations consisted of different levels of corn gluten feed (0%, 20%, 35% and 50%) as corn substitution. The portion of corn was 30% in grower ration and 25% in finisher ration. A completely randomized design was used in this research. Slaughtered weight, carcass weight, carcass percentage, carcass length, backfat thickness and loin eye area were observed. The data were analyzed by analysis of variance. The results showed that corn gluten feed did not significantly affect all parameters of carcass quality. Economic analysis showed that the use of corn gluten feed as corn substitution on swine rations produced lower profit. Key words : corn gluten feed, carcass quality, swine